Percutaneous Embolization of Biliary Leaks: A Systematic Interdisciplinary Review and Proposal for a New Classification - Schmitz, Daniel; Mutignani, Massimiliano; Neumann, Ulf Peter; Wielpütz, Mark Oliver; Hagenmüller, Friedrich; Rudi, Jochen; Chang, De-Hua (Digestive Disease Interventions, 2020)
Objectives Biliary leak can be treated by percutaneous biliary embolization. The aim of this systematic interdisciplinary review was to analyze available reports on percutaneous embolization of biliary leak.Methods We used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach to perform literature database search. The following terms were systematically analyzed: type of embolic agent, success rates, embolization-related adverse events, cause of biliary leak, fistula connection type, anatomic bile duct variants, and access routes.Results Of 713 publications identified, 45 reports with 101 patients were included. Six temporary and 4 permanent embolic agents were used in 55/101 (54.5%) and 46/101 (45.5%) patients; combined in 18/101 patients (17.8%). Bile leak was successfully embolized in 97/101 (96.0%) patients, in 48/101 (47.5%) patients after repeated procedures with the same agent, and in 4/101 (3.9%) patients after a failed embolization with other agents: isolated bile duct fistula (n = 2), intrahepatic fistula after liver resection, and biliary-bronchial fistula. Five types of biliary leak were associated with the following success rates: (A) common bile duct (CBD) or cystic duct: 4/4 (100%); (B) intrahepatic bile duct (IHBD), communicating with CBD: 16/18 (88.9%); (C) isolated IHBD: 49/51 (96%); (D) CBD or cystic duct, bile duct system (BDS) not accessible by endoscopic retrograde cholangiopancreatography (ERCP): 7/7 (100%); and (E) IHBD, communicating with CBD, BDS not accessible by ERCP: 9/9 (100%).Conclusions Embolization was highly successful without clear preference for one embolic agent. A new classification of biliary leak is proposed to direct nonsurgical treatments.
Keywords: embolization; fistula; therapeutic; radiology; interventional; cholangiopancreatography; endoscopic retrograde